Peran pelatihan desain grafis dalam mewujudkan pemuda rentan yang memiliki keterampilan dan kemandirian - Febrina Sari; Tri Handayani; Soni Fajar Mahmud (Unri Conference Series: Community Engagement, 2019)
Out-of-school children are Vulnerable Youth who usually spend their days hanging out on the roadside or at crossroads and at patrol posts, this is because they are still unproductive (not working). Some vulnerable youths have worked but only as unskilled labourers with wages of 40-60 thousand rupiah per day, compared to other villages, school dropouts/vulnerable young people in Bukit Kayu Kapur Village have a higher percentage of 7%, which is 114 people, from the total productive population in 1630. This is because Vulnerable Youth do not have the specific knowledge and skills to be able to work and get better wages. The Community Stimulus Partnership Program has been implemented in an effort to empower young people who are vulnerable to dropping out of school to reduce the number of unemployed people without skills. This effort is to provide graphic design training for vulnerable youth. The results that have been achieved in the Stimulus Partnership Program activities are the increased knowledge of members of vulnerable youth groups about the use of computers and vulnerable youth who have skills in designing several products such as banners, banners, business cards, invitations, calendars and brochures.